Static and dynamic emulation analysis on frame structure of farm tricycle - MA Guang; HUANG Dong-ming; WANG Zhi-ming (浙江大学学报. 农业与生命科学版)
Static and dynamic emulation analysis on a new type of frame construction of solar battery farm tricycle was performed. CAD model was built with the Pro/e software. Frame finite element model (FEM) was established with shells as a basic unit, and the analysis of static, dynamic and random vibrations were carried out by the MSC. Patran/Nastran software. The static and dynamic characteristics of the frame were obtained, The results indicated that static stress was abundant, and the dynamic stress exceeds permissive stress. The inherent frequency and inherent vibrant former of the frame was good. It brought forward the improving configuration and validated it. The maximal static and dynamic stress in hold still status and brake status was less than the one that had not been improved. The first rank inherent frequency of the frame was bigger but the probability of resonance was lower. The saltation of vibrant former was eliminated. The Static and dynamic capability was improved. The analysis results provided the theory basement for the frame improvement.